2019
DOI: 10.1186/s13063-019-3376-6
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of the In2Care® auto-dissemination device for reducing dengue transmission: study protocol for a parallel, two-armed cluster randomised trial in the Philippines

Abstract: Background Mosquito-borne viruses are imposing an ever increasing health burden worldwide. In addition to the recent Zika and chikungunya virus epidemics, dengue viruses have become the fastest growing problem with a 40-fold increase in the number of reported cases over the past five decades. Current mosquito control techniques involving larval source reduction, larviciding, and space spray of adulticides are costly, laborious, and of debatable efficacy. There remains an urgent need for the develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 49 publications
(61 reference statements)
0
7
0
Order By: Relevance
“…Trap and lure combinations were tested in an SFS house trial with the aim of improving future mosquito surveillance. Trap and lure combinations have been successfully applied to the control of several insect taxa, including mosquitoes [ 26 ] and tsetse flies [ 27 ]. Although traps are important tools for the surveillance of mosquito abundance [ 9 ], most of them are relatively ineffective, and especially so for day-biting mosquitoes such as Ae.…”
Section: Discussionmentioning
confidence: 99%
“…Trap and lure combinations were tested in an SFS house trial with the aim of improving future mosquito surveillance. Trap and lure combinations have been successfully applied to the control of several insect taxa, including mosquitoes [ 26 ] and tsetse flies [ 27 ]. Although traps are important tools for the surveillance of mosquito abundance [ 9 ], most of them are relatively ineffective, and especially so for day-biting mosquitoes such as Ae.…”
Section: Discussionmentioning
confidence: 99%
“…When combined with a source reduction program, the In2Care mosquito trap could be an integral component of a ''push-pull'' strategy to control container-breeding Aedes by attractive oviposition lures (pull) (Cook et al 2007). Since inauguration, some limited field evaluations have been conducted (Farenhorst 2015), and promising results with variabilities have been reported (Snetselaar et al 2014, Buckner et al 2017, Salazar et al 2019. Following the detections and population increase of Ae.…”
Section: Introductionmentioning
confidence: 99%
“…One of the most effective ways to reduce dengue cases is to manage the vector that carries the DENV. The use of AD-PPF as a strategy to control mosquito density has been proven effective based on previous research [39][40][41]. In the Philippines, previous research tackled the use of AD-PPF in a small urban community in Metro Manila using a small sample size in which results showed that dengue seroconversion rates decreased in the treated population but not significantly so.…”
Section: Discussionmentioning
confidence: 99%